Overexpression of lipocalin 2 in PBX1‐deficient decidual NK cells promotes inflammation at the maternal‐fetal interface. (15th January 2023) - An, Xue; Qin, Jingkun; Hu, Xinyu; Zhou, Yonggang; Fu, Binqing; Wei, Haiming
Abstract: Problem: Impairment of PBX1 expression in decidual natural killer (dNK) cells is associated with the pathogenesis of unexplained recurrent spontaneous abortion, which results in fetal growth restriction (FGR) by affecting the secretion of downstream growth factors. However, whether other mechanisms limit embryo growth in decidua containing PBX1 ‐deficient natural killer (NK) cells is unknown. Method of study: Pbx1 f/f ; Ncr1 Cre mice were employed to explore the underlying mechanisms by which PBX1 − NK cells affect embryonic development. To simulate the clinical testing of pregnant women, Doppler ultrasound imaging was used to detect embryo implantation and development. Differentially expressed genes (DEGs) in PBX1 − NK cells that may affect normal pregnancy were screened using RNA‐sequencing and real‐time PCR. Immune cell changes caused by DEGs were detected by flow cytometry. Finally, the mechanism of FGR was explored by injecting the protein LCN2, corresponding to the selected DEG, into mice. Results: We verified the embryonic dysplasia in pregnant Pbx1 f/f ; Ncr1 Cre mice by Doppler ultrasound imaging and found that LCN2 was upregulated in dNK cells. We also observed higher infiltration of neutrophils and macrophages in the decidua of Pbx1 f/f ; Ncr1 Cre mice. Finally, we found an increase in the number and activation of neutrophils at the maternal‐fetal interface after injecting LCN2 into pregnant mice and observed that these mice showed signs of FGR. Conclusion: Excessive LCN2 secreted by PBX1 − dNK cells at the maternal‐fetal interface recruit neutrophils and causes an inflammatory response, which is related to FGR.